2015
DOI: 10.7439/ijasr.v1i7.2251
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Evaluation of Lecithin Organogel for Treatment of Arthritis

Abstract: Background: Arthritis is a disease of the joint that involves inflammation of one or more joints. Topical administration of NSAIDs could deliver lornoxicam to the site of action in rheumatic diseases, which would reduce the gastrointestinal complications and side effects of the drug. Methods: In this method, the oily phase was prepared by dispersing the specific amount (ratio; 40:60) of purified lecithin at room temperature in isopropyl myristate as dispersing and emulsifying agent. The aqueous phase of polypr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Recently gel formulation have been modified to yield an advance drug delivery system known as -organogels‖. [4] It was found that lipid based formulation work most efficiently by improving penetration through the skin but drawback with such formulation is that they alter the hydration state to skin, cause dermatitis. On the other hand, water based formulation able to maintain bioactive state of skin but exhibit poor penetration.…”
Section: Gelmentioning
confidence: 99%
“…Recently gel formulation have been modified to yield an advance drug delivery system known as -organogels‖. [4] It was found that lipid based formulation work most efficiently by improving penetration through the skin but drawback with such formulation is that they alter the hydration state to skin, cause dermatitis. On the other hand, water based formulation able to maintain bioactive state of skin but exhibit poor penetration.…”
Section: Gelmentioning
confidence: 99%
“…Recently, attempts are being made to modify gel formulation by developing organogel which is solely a gelled homogeneous mixture of non-ionic surfactant with a non-polar organic solvent or vegetable oil at room temperature [6]. Organogel is a thermodynamically stable, viscoelastic system comprising of a gelator (any substance capable of forming gel) and a nonpolar phase (non-aqueous), with or without the presence of water molecules within the network formed by the gelator system [7].…”
Section: Introductionmentioning
confidence: 99%